2015
DOI: 10.1371/journal.pone.0119568
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation Response in Chronic HIV-Infected Patients: Influence of Hepatitis C Virus Coinfection

Abstract: ObjectivesWe have analyzed the parameters (bacterial translocation, immune activation and regulation, presence of HCV coinfection) which could be implicated in an inappropriate immune response from individuals with chronic HIV infection. The influence of them on the evolution of CD4+ T cell count has been investigated.Patients and methodsSeventy HIV-infected patients [monoinfected by HIV (n = 20), HCV-coinfected (with (n = 25) and without (n = 25) liver cirrhosis)] and 25 healthy controls were included. Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…A small study reported evidence of higher tissue factor activity (measured as microparticles tissue factor), a procoagulant factor, and associated CD4 T cell activation in HCV patients both mono- and HIV-coinfected suggesting a potential mechanism of immune activation and coagulopathy that may predispose to cardiovascular disease [86]. In another prospective study, immune activation markers were compared between HIV monoinfecetd and HIV/HCV coinfected (with and without cirrhosis) ART treated patients with suppressed plasma HIV viremia during 12 months [87]. HIV patients with chronic hepatitis and cirrhosis had higher concentrations of serum sCD14 and IL-6 and incomplete CD4 restoration.…”
Section: Cryptococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…A small study reported evidence of higher tissue factor activity (measured as microparticles tissue factor), a procoagulant factor, and associated CD4 T cell activation in HCV patients both mono- and HIV-coinfected suggesting a potential mechanism of immune activation and coagulopathy that may predispose to cardiovascular disease [86]. In another prospective study, immune activation markers were compared between HIV monoinfecetd and HIV/HCV coinfected (with and without cirrhosis) ART treated patients with suppressed plasma HIV viremia during 12 months [87]. HIV patients with chronic hepatitis and cirrhosis had higher concentrations of serum sCD14 and IL-6 and incomplete CD4 restoration.…”
Section: Cryptococcusmentioning
confidence: 99%
“…HIV patients with chronic hepatitis and cirrhosis had higher concentrations of serum sCD14 and IL-6 and incomplete CD4 restoration. Although the percent of activated CD4+ and CD8+ T cells and Treg were higher in HIV-infected patients compared to healthy controls, no significant differences were observed among the groups of HIV patients [87]. In a different study, biomarkers of inflammation including INFa were found to be higher in HCV/HIV co-infected patients compared to HCV mono-infected patients but importantly, some decreased after successful sustained virologic suppression (SVR) of hepatitis C [88].…”
Section: Cryptococcusmentioning
confidence: 99%
“…Much evidence has suggested that elevated plasmatic levels of soluble CD14 (sCD14) are indicative of bacterial translocation . Recent studies have demonstrated a relationship between sCD14 and hepatic disease outcomes in chronically HCV‐infected individuals . In this study, sCD14 concentrations were not only elevated in plasma from naive and therapy failed CHC patients (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…These studies have suggested that high levels of BT markers are frequently found in HIV/HCV‐coinfected patients, underpinning the severity of the underlying liver fibrosis. Besides, HIV/HCV‐coinfected patients with decompensated cirrhosis had higher levels of BT and immune activation markers in one study . Because of the above‐mentioned reasons, it is reasonable to speculate that BT might contribute to a worse clinical outcome in HIV‐infected patients with advanced liver disease due to HCV.…”
Section: Introductionmentioning
confidence: 93%
“…Besides, HIV/HCV-coinfected patients with decompensated cirrhosis had higher levels of BT and immune activation markers in one study. 13 Because of the above-mentioned reasons, it is reasonable to speculate that BT might contribute to a worse clinical outcome in HIV-infected patients with advanced liver disease due to HCV. Thus, our objective was to assess whether BT impacts on the clinical outcome of compensated cirrhosis in HIV/HCV-coinfected patients.…”
Section: Introductionmentioning
confidence: 99%